-6=-4x+7x

Simple and best practice solution for -6=-4x+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=-4x+7x equation:


Simplifying
-6 = -4x + 7x

Combine like terms: -4x + 7x = 3x
-6 = 3x

Solving
-6 = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-6 + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
-6 + -3x = 0

Add '6' to each side of the equation.
-6 + 6 + -3x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -3x = 0 + 6
-3x = 0 + 6

Combine like terms: 0 + 6 = 6
-3x = 6

Divide each side by '-3'.
x = -2

Simplifying
x = -2

See similar equations:

| (6x+11)*log(4)=(x-1)*log(16) | | 103=8(7-m)+7 | | 4n+42+n-100=2942 | | 103=8(3n-2)-3(4+n) | | 4z=1.7+4.3 | | x^2-3*x=22 | | x^2-3*tan(4*3x)=12 | | 5+3a+3=23 | | 0.8p=-112 | | x+9-2sqrtx+24=0 | | log(5x+7)=1+log(x-6) | | 7y=6(y+6) | | 3x-4x=65 | | 5(2+3x)-1=-6 | | (x+3y)(5x+3y)= | | (4y+2)(4-y)=0 | | 2z=1.8+0.8 | | 56=14y-7y | | (3y^2-5y+2)-(3y^6)=19 | | -0.4x=-12 | | 9n+6+5n-31=203 | | 5t^3+6t^2-10t-12=0 | | 3x-3=-3-3 | | 2-b=16 | | 3(5x+2)=3*5x+3*2 | | 1.5=3y+11.1 | | 45a+18ac=a | | 2(3x-12)=3(2x+10) | | 3n+3.1=8.2 | | 4(-2)squared+8(-2)squared+3(-2)squared+6= | | 4x+16=2(x+8) | | y=-2x-19 |

Equations solver categories